2017
DOI: 10.1111/jzo.12467
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compound secretion coincides with modifications of the olfactory organ in mantellid frogs

Abstract: Madagascar frogs (Mantellidae) contain species with derived mating behaviour and femoral macroglands secreting volatile pheromones. Here, we screen 28 mantellid species to show that volatile compounds are present in at least five genera with femoral glands, while no such compounds were found in genera devoid of these glands. The nasal cavity of volatile‐producing species of four genera showed a derived state, with partial or almost complete obstruction of the connection between main olfactory organ (MOO) and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…phoracantholide J ( 4 ),[1,2] gephyromantolide A ( 1 ),[1] mantidactolides ( 5 , 6 ),[3] or other macrolides with even larger rings ( 2 ). [4,5] Further studies have provided evidence that macrolactones can actually be perceived by the olfactory system of mantellids[6] and that these frogs contain species-specific mixtures of volatiles despite occasional large variations within species. [2,6]…”
Section: Introductionmentioning
confidence: 99%
“…phoracantholide J ( 4 ),[1,2] gephyromantolide A ( 1 ),[1] mantidactolides ( 5 , 6 ),[3] or other macrolides with even larger rings ( 2 ). [4,5] Further studies have provided evidence that macrolactones can actually be perceived by the olfactory system of mantellids[6] and that these frogs contain species-specific mixtures of volatiles despite occasional large variations within species. [2,6]…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of the olfactory system in adult stages has been studied in great detail in ranids (Døving, Trotier, Rosin, & Holley, ; Gaupp, ; McCotter, ; Tsui, ), in basal anurans (Benzekri & Reiss, ; Stephenson, ; Wagner, ), and in pipids (Dittrich, Kuttler, Hassenklöver, & Manzini, ; Hansen et al, ; Paterson, ; Reiss & Burd, , among others), as well as in surveys across anurans (Helling, ; Jurgens, ). These studies have shown that the general morphology and organization of this system are shared by the majority of anurans, with the exception of the pipids and ascaphids, in which certain morphological peculiarities have been described as related to the aquatic habits of adults (Paterson, ; Reiss & Eisthen, ), and in the recently described deviant anatomy of the mantellid Mantidactylus betsileanus (Junk et al, ; Nowack & Vences, ), where the functional significance appears to relate to perception of femoral gland pheromone secretions (Nowack et al, ). The analysis of the adult morphology of the nose in ceratophryid frogs also reveals a somewhat deviant morphology in adult stages of the aquatic Lepidobatrachus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Dichloromethane was used as solvent to extract out the skin gland secretion ( Nowack et al, 2017 ). The dissected skin samples (n = 3) were separately kept in dichloromethane for 48 h. Thereafter, the skin was trashed and the dichloromethane was filtered to remove the debris ( Poth et al, 2012 , Poth et al, 2013 ) and injected to GC MS. Gas chromatography/mass spectrometry analysis was done on Agilent Technologies 7890A GC (Germany) with Column db5 MS (30 m 0.25 mm I.D., 0.25 µm), flow rate 1.5 mL/min and helium as carrier gas.…”
Section: Methodsmentioning
confidence: 99%